Study on Concentrating Characteristics of a Solar Parabolic Dish Concentrator within High Radiation Flux - Qianjun Mao; Liya Zhang; Hongjun Wu (International Journal of Photoenergy)
Concentrating characteristics of the sunlight have an important effect on the optical-thermal conversion efficiency of solar concentrator and the application of the receiver. In this paper, radiation flux in the focal plane and the receiver with three focal lengths has been investigated based on Monte Carlo ray-tracing method. At the same time, based on the equal area-height and equal area-diameter methods to design four different shape receivers and numerical simulation of radiation flux distribution characteristics have also been investigated. The results show that the radiation flux in the focal plane increases with decreasing of the focal length and the diameter of the light spot increases with increasing of the focal length. The function of the position with a maximum of radiation flux has been obtained according to the numerical results. The results also show that the radiation flux distribution of cylindrical receiver has the best performance in all four receivers. The results can provide a reference for future design and application of concentrating solar power.